The role of convection in the buildup of the ring current pressure during the 17 March 2013 storm. Issue 1 (21st January 2017) - Menz, A. M.; Kistler, L. M.; Mouikis, C. G.; Spence, H. E.; Skoug, R. M.; Funsten, H. O.; Larsen, B. A.; Mitchell, D. G.; Gkioulidou, M.
Abstract: On 17 March 2013, the Van Allen Probes measured the H + and O + fluxes of the ring current during a large geomagnetic storm. Detailed examination of the pressure buildup during the storm shows large differences in the pressure measured by the two spacecraft, with measurements separated by only an hour, and large differences in the pressure measured at different local times. In addition, while the H + and O + pressure contributions are about equal during the main phase in the near‐Earth plasma sheet outside L  = 5.5, the O + pressure dominates at lower L values. We test whether adiabatic convective transport from the near‐Earth plasma sheet ( L  > 5.5) to the inner magnetosphere can explain these observations by comparing the observed inner magnetospheric distributions with the source distribution at constant magnetic moment, mu. We find that adiabatic convection can account for the enhanced pressure observed during the storm. Using a Weimer 1996 electric field we model the drift trajectories to show that the key features can be explained by variation in the near‐Earth plasma sheet population and particle access that changes with energy and L shell. Finally, we show that the dominance of O + at low L shells is due partly to a near‐Earth plasma sheet that is preferentially enhanced in O + at lower energies (5–10 keV) and partly due to the time dependence in the source combined with longer drift times to low L shells. No source of O + inside L  = 5.5 is required to explain the observations at low L shells. Key Points: Adiabatic inward convection of the near‐Earth plasma sheet causes the ring current pressure enhancements Pressure enhancements are dominated by the highest energies able to convect to low L shells O + rich source during main phase causes O + dominance in lower L shells